2016
DOI: 10.1103/physrevd.93.083505
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological bounds on TeV-scale physics and beyond

Abstract: We study the influence of the fluctuations of a Lorentz invariant and conserved vacuum on cosmological metric perturbations, and show that they generically blow up in the IR. We compute this effect using the Källén-Lehmann spectral representation of stress correlators in generic quantum field theories, as well as the holographic bound on their entanglement entropy, both leading to an IR cut-off that scales as the fifth power of the highest UV scale (in Planck units). One may view this as analogous to the Heise… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…It links two completely different and independent calculations. One is implementing quantum effects into a gravitational theory by means of effective quantum field theory and the other solving the modified Friedmann equations (10,11) subject to a simple energy condition (16). The support of both approaches is mutual.…”
Section: Comparison With the Functional Renormalization Groupmentioning
confidence: 99%
“…It links two completely different and independent calculations. One is implementing quantum effects into a gravitational theory by means of effective quantum field theory and the other solving the modified Friedmann equations (10,11) subject to a simple energy condition (16). The support of both approaches is mutual.…”
Section: Comparison With the Functional Renormalization Groupmentioning
confidence: 99%
“…Such an effect could be exactly what is needed to cure the issues noticed in Ref. 34, where it has been shown that quantum fluctuations in the energy-momentum tensor of matter can cause serious phenomenological problems. The latter could however be avoided provided at high energies exists a field like χ that compensates the effects of the matter fluctuations.…”
Section: Discussion and Outlookmentioning
confidence: 87%
“…If Λ comes from quantum gravitational effects or fundamental discreteness of spacetime [13][14][15], we expect it to be around Planck energy, M P . On the other hand, a priori, Λ can be much smaller than M P , even as low as ∼ 10 TeV, as suggested in large extra dimension models that are constructed to address the hierarchy problem (e.g., [16]), or by the cosmological non-constant problem [17]. However, in this paper we assume Λ H inf , i.e.…”
Section: Review Of Of Dmmentioning
confidence: 98%